Recent Studies on the Effects of Static Magnetic Fields (SMF) on Reproductive Function - Chengchang Zhang; Chengle Dong; Xiaohang Liu; Jiaxing Zhang; Qinlan Li; Shuting Chen; Hu Zhao; Donghui Huang (Current Issues in Molecular Biology)
Background: With the widespread use of static magnetic fields (SMFs) in applications such as magnetic resonance imaging (MRI) and electric vehicles, concerns have arisen regarding their potential effects on reproductive health. Despite increasing research, the impact of SMFs on reproductive function remains a subject of debate, requiring further exploration. Methods: This review synthesizes animal and clinical studies on the effects of SMF on reproductive function. It examines various SMF intensities and exposure durations, focusing on mitochondrial function, chromosomal division, and embryonic development. Results: The review reveals that low-intensity SMF exposure adversely affects mitochondrial function in sperm and eggs, reducing their activity. It also impacts follicular cells, delaying chromosomal division. Medium- and high-intensity SMF exposure shows mixed results, with both potential benefits and risks, requiring further research. High-intensity SMFs may pose teratogenic risks to embryos and delay the development of fertilized eggs. The position of SMF exposure also matters, likely due to field non-uniformity. Conclusions: This review provides a foundation for further investigation into the effects of SMFs on reproductive function, highlighting the need for more comprehensive studies to assess safety and applications. Special caution is advised for pregnant women regarding SMF exposure, given its potential risks.